Evaluation of Serum Transaminase Levels Changes in Patients with Dengue Hemorrhagic Fever - Thi Quynh, Do; Thi Thu Hoai, Bui; Thi Thuy An, Pham; Thi Huong, Duong; Thi Minh Phuong, Le; Van Nga, Vu (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 1, 2025)
Dengue hemorrhagic fever (DHF) is one of the most important diseases mosquitoes transmit due to its rapid spread and economic burden. DHF affects many organs in the body such as the liver, heart, and kidney. The liver damage results in the elevation of serum transaminases. This study aimed to assess the changes in serum aminotransferase levels (aspartate aminotransferase - AST and alanine aminotransferase - ALT) in DHF patients with or without warning signs and related factors. A cross-sectional study was conducted in the E hospital in 2019. Based on the guidelines of the World Health Organization (WHO) 2016, clinical information, medical history, and several laboratory results (complete blood count, ALT, AST, and dengue serology) were collected. 302 patients diagnosed with DHF were included in this study. 59.9% of patients had warning signs, and 40.1% of patients were without warning signs. 57.6% of patients had elevated AST and 36.8% of patients had elevated ALT. Both AST and ALT increased from the febrile phase (days 1 to 3) and were higher in the critical phase (days 4 to 7) of Dengue. Mean AST and ALT levels in two groups with and without warning signs were 79.75 ± 59.85 U/L and 111.53 ± 181.10 U/L, 51.61 ± 46.49 U/L and 74.64 ± 108.08 U/L, respectively. There was no correlation between the severity of Dengue with gender, age groups, BMI, history of biliary liver disease, and history of Dengue. Transaminase levels were higher in patients with decreased platelet counts, especially in the critical phase (days 4-7) (p < 0.05). Hepatic dysfunction was prevalent in Dengue patients. Serum aminotransferase levels increased from the early stages of the disease. There was a correlation between transaminases and the severity of Dengue fever.